[(-3)⁷]²:(-3)¹¹+(-2)×(-2)²×(-2)³÷(-2)⁴=?
va roggggg
Răspunsuri la întrebare
Răspuns de
1
(-3)^3 + (-2)^2 =
-27 + 4 =
-23
-27 + 4 =
-23
emiionita10:
ms<3
Răspuns de
1
Răspuns:
[(-3)⁷]²:(-3)¹¹+(-2)×(-2)²×(-2)³:(-2)⁴ =
(-3)⁷ˣ²:(-3)¹¹+(-2)¹⁺²⁺³⁻⁴ =
(-3)¹⁴:(-3)¹¹+(-2)² =
(-3)¹⁴⁻¹¹ +4 =
(-3)³+4=
-27+4=
-23
Alte întrebări interesante
Istorie,
8 ani în urmă
Germana,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Biologie,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă